ANALISIS DIGITAL MARKETING DAPAT MENINGKATKAN PURCHASE INTENTION PRODUK UMKM MELALUI CONTENT MARKETING DI KABUPATEN PENAJAM PASER UTARA - Rohman, Dwi Taufik; Nurlia, Nurlia; Hardinata, Ega; Noor Yudha, Muhamad (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
This study aims to analyze the influence of digital marketing on the purchase intention of MSME products in Tengin Baru Village, Penajam Paser Utara Regency, with content marketing as a mediator. The method used is SEM-PLS with Smart PLS 3.0, testing the relationship between digital marketing, content marketing, and the purchase intention of MSME consumers. The research results show that digital marketing has a significant effect on purchase intention with a path coefficient of 0.786, and a strong influence on content marketing with a path coefficient of 0.812. Additionally, content marketing mediates the effect of digital marketing on purchase intention with a path coefficient of 0.296, though its influence is smaller compared to the direct effect of digital marketing. The discussion reveals that digital marketing strategies are crucial for MSMEs to increase consumer purchase intention. Content marketing plays an important role as a mediator, strengthening the influence of digital marketing by building closer relationships with consumers and increasing brand awareness. These findings are consistent with previous research that emphasizes the importance of content marketing in maximizing digital marketing strategies. In conclusion, digital marketing has proven to be effective in enhancing purchase intention, especially when supported by engaging and relevant content marketing. Therefore, MSMEs in Penajam Paser Utara should prioritize digital marketing while enhancing content strategies to maximize their impact on consumer purchase intention. For future research, MSMEs in this region are advised to continue developing digital marketing strategies and improve their literacy and skills in creating effective content marketing to strengthen their influence on consumer purchase intention.